Komunikasi Digital dan Pemberdayaan Sosial : Analisis Penggunaan Media Sosial pada Komunitas Lokal - Fatimah; Suparman; Arsyad; Mandjarreki, Sakarudin (Jurnal Dakwah Tabligh, 2025)
This article discusses the role of digital communication, particularly through social media, in the process of social empowerment by local communities. This study uses a qualitative approach with a case study on the youth community in Tungka Village, Enrekang. The results show that the use of social media such as Instagram and WhatsApp is strategically able to increase member participation, build a wider social network, and strengthen the collective identity of the community. In addition to being a tool for disseminating information, social media is also a space for discussion, negotiation of meaning, and decision-making among community members, which ultimately encourages collaboration and social solidarity. However, challenges such as limited digital literacy and access to infrastructure are obstacles that need to be overcome so that digital communication can take place effectively and inclusively. This article recommends strengthening digital literacy, training on the use of social media, and increasing access to technology as important strategies to support the effectiveness of empowerment communication at the grassroots level. These findings are expected to make practical and theoretical contributions to the development of digital technology-based social empowerment in local communities.